Optical fiber fluorescence sensor and fluorescence detection system
By assembled the golden nano -particle layer and intervals on the surface of the cone fiber fluorescent sensor, optimize the coupling of the LSPR resonance field and fluorescent and fiber, solve the problem of low signal -to -noise ratio and poor sensitivity of traditional fiber fluorescence sensors, and realize the signal -to -noise ratio Increase the effect by 2-3 times.
Patent Information
- Application Number
- CN202411496181.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional fiber optic fluorescence sensors have low signal-to-noise ratio and poor sensitivity, making it difficult to achieve efficient fluorescence detection in biological organisms.
Design a kind of cone fiber fluorescent sensor, the surface of which is assembled with golden nanometer layer, and forms a partition layer on the surface of the gold nano particles. By controlling the spacing of golden nanoparticles and the thickness of the intervals, optimize the LSPR resonance field and fluorescent fluorescent field Coupling of optical fiber.
The signal-to-noise ratio of the optical fiber fluorescence sensor is effectively improved, and the sensitivity has increased by 2-3 times, which significantly improves the performance of fluorescent detection.
Smart Images

Figure CN119375192A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fluorescence detection, and in particular to an optical fiber fluorescence sensor and a fluorescence detection system. Background Art
[0002] As a commonly used detection method in the biomedical field, fluorescence detection has attracted much attention since its birth. In the following decades, fluorescence-based detection methods have emerged one after another. The main means of fluorescence detection at present are fluorescence microscopes, fluorescence photometers, etc., but due to the limitations of factors such as their size, they are unable to cope with in vivo real-time detection such as in vivo. As an excellent light-guiding medium, optical fiber has been widely used in many fields such as environment, industry and biomedicine due to its advantages such as small size, light weight, low transmission loss, strong resistance to electromagnetic interference and chemical corrosion. It has become the latest choice for various types of sensors. Compared with traditional sensors, it has the following advantages: good stability, fast response speed, miniaturization, easy integration, can be used for detection in dangerous and harsh environments, and can realize real-time dynamic monitoring on site. Therefore, the use of optical fiber sensors as fluorescence detection has gradually become an important detection technology.
[0003] As early as 1977, researchers used fiber optic sensors to achieve in-situ detection of substances in living organisms. In recent years, some scholars have achieved in-situ detection and real-time ablation of mouse tumor cells. However, the spontaneous fluorescence in living organisms, the tiny size of optical fibers, and the weak collection efficiency make the signal-to-noise ratio of fiber optic fluorescence detection relatively low.
[0004] Using the evanescent wave generated by the side wall of the tapered optical fiber to stimulate fluorescence detection can improve the signal-to-noise ratio of fluorescence detection. For example, the evanescent field generated by the side wall of the tapered optical fiber can be used to excite the gold particles assembled on the surface of the optical fiber to generate localized surface plasmon resonance (LSPR) to further improve the signal-to-noise ratio of optical fiber fluorescence collection. However, although the introduction of LSPR in the tapered optical fiber can generate an extremely strong local electromagnetic field and improve the signal-to-noise ratio of the sensor. However, the following problems still exist: 1. The side wall of the tapered optical fiber needs to generate a sufficiently strong evanescent field to excite the LSPR. At the same time, the arrangement of the metal particles assembled on the side wall of the optical fiber not only affects the strength of the LSPR field, but also affects the coupling between the fluorescence and the optical fiber; 2. Resonant energy transfer will occur between the metal particles and the fluorescent group, resulting in fluorescence quenching, affecting the detection of fluorescence signals.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a fiber optic fluorescence sensor and a fluorescence detection system. The fiber optic fluorescence sensor of the present invention effectively solves the shortcomings of low signal-to-noise ratio and poor sensitivity of traditional fiber optic fluorescence sensors. Compared with traditional fiber optic fluorescence sensors, the detection signal-to-noise ratio can be increased by 2-3 times.
[0007] In a first aspect, the present invention provides an optical fiber fluorescence sensor, which is a tapered optical fiber sensor, and a gold nanoparticle layer is self-assembled on the surface of the tapered optical fiber of the optical fiber fluorescence sensor, and a spacer layer is self-assembled on the surface of the gold nanoparticle layer.
[0008] Wherein, in the gold nanoparticle layer, the spacing between the gold nanoparticles is 50-70 nm, and the thickness of the spacer layer is 5-15 nm, and preferably 8 nm.
[0009] Studies have shown that the arrangement of metal particles assembled on the side wall of the optical fiber not only affects the strength of the LSPR field, but also affects the coupling between fluorescence and optical fiber. When the metal particles are dense, the LSPR resonance field is strong, but the coupling between fluorescence and optical fiber is weak, so that the fluorescence cannot be detected; when the metal particles are sparse, the LSPR resonance field is weak, the coupling between fluorescence and optical fiber is strong, but the fluorescence enhancement is weak or even cannot be enhanced, resulting in a low signal-to-noise ratio of the sensor. The present invention can achieve the best coupling between the LSPR resonance field and fluorescence and optical fiber by controlling the arrangement of gold nanoparticles.
[0010] In addition, the study found that when the distance between the fluorescent group and the metal particle is less than 5nm, resonance energy transfer will occur between the metal particle and the fluorescent group, resulting in fluorescence quenching, affecting the fluorescence signal detection. Therefore, the present invention further proposes to use a layer-by-layer (LBL) method to assemble a spacer layer on the surface of the metal particle to prevent the quenching of the fluorescent group.
[0011] Therefore, the fiber optic fluorescence sensor based on LSPR enhanced fluorescence of the present invention effectively solves the shortcomings of low signal-to-noise ratio and poor sensitivity of traditional fiber optic fluorescence sensors through the structural design of the tapered optical fiber, the arrangement of gold nanoparticles and the setting of the spacer layer. Compared with traditional fiber optic fluorescence sensors, the detection signal-to-noise ratio is improved by 2-3 times.
[0012] As a preferred embodiment of the present technical solution, the material of the spacer layer is polyallylamine hydrochloride / sodium polystyrene sulfonate. Using polyallylamine hydrochloride / sodium polystyrene sulfonate polymer as the spacer layer between the gold nanoparticle layer and the fluorescent group can effectively prevent quenching of the fluorescent group.
[0013] As a preferred embodiment of the present technical solution, the waist length of the optical fiber fluorescence sensor is 200-400 μm, and preferably 300 μm, and the detection area length is 1-3 mm, and preferably 2 mm.
[0014] Studies have shown that this conical-structured fiber optic fluorescence sensor can generate an LSPR evanescent field by exciting gold particles. On the one hand, the LSPR evanescent field can generate an extremely strong local electromagnetic field, which increases the radiation decay rate of the fluorescent group and greatly enhances the fluorescence intensity. On the other hand, the LSPR evanescent field can further effectively reduce the interference of background spontaneous fluorescence, thereby improving the signal-to-noise ratio of the fiber optic fluorescence sensor.
[0015] As a preferred embodiment of the present technical solution, the preparation of the gold nanoparticle layer comprises the following steps:
[0016] S1, treating the optical fiber surface of the optical fiber fluorescence sensor to hydroxylate the optical fiber surface;
[0017] S2. The surface hydroxylated optical fiber is sequentially immersed in a tetrahydrofuran solution of polystyrene-b-poly(4-vinylpyridine) and a spherical gold nanoparticle solution to obtain a gold nanoparticle layer by self-assembly on the surface of the optical fiber.
[0018] Specifically, in step S1, the optical fiber surface of the optical fiber fluorescence sensor can be treated with piranha solution to remove organic matter on the optical fiber surface and hydroxylate the optical fiber surface, thereby improving its hydrophilicity and improving the surface foundation for subsequent modification.
[0019] In step S2, the optical fiber with surface hydroxylation is immersed in a tetrahydrofuran solution of polystyrene-b-poly (4-vinyl pyridine), and after keeping for a certain time, the polystyrene-b-poly (4-vinyl pyridine) (PS-b-P4VP) molecules can be adsorbed on the optical fiber surface and form a monolayer. Afterwards, the optical fiber is taken out and cleaned with a suitable solvent to remove the non-absorbed polystyrene-b-poly (4-vinyl pyridine) (PS-b-P4VP) molecules. The surface of the gold nanoparticles usually carries negatively charged citrate to enhance its stability and dispersibility in aqueous solution. Therefore, when the optical fiber is further immersed in a solution of spherical gold nanoparticles, it is kept for a certain time, so that the spherical gold nanoparticles can be adsorbed on the monolayer of polystyrene-b-poly (4-vinyl pyridine) (PS-b-P4VP) on the optical fiber surface and form a self-assembled monolayer. Afterwards, the optical fiber is taken out and cleaned with a suitable solvent to remove the non-absorbed gold nanoparticles.
[0020] As a preferred embodiment of the present invention, the concentration of the tetrahydrofuran solution of polystyrene-b-poly(4-vinylpyridine) is 0.002-0.010 mg / mL, and preferably 0.005 mg / mL, the immersion temperature is 20-30°C, and preferably 25°C, and the immersion time is 5-15 min, and preferably 10 min.
[0021] As a preferred embodiment of the present technical solution, the concentration of the spherical gold nanoparticle solution is 0.001-0.008 mg / mL, and preferably 0.004 mg / mL, the immersion temperature is 20-30° C., and preferably 25° C., and the immersion time is 10-15 h.
[0022] As a preferred embodiment of the present technical solution, the preparation of the spacer layer includes the following steps:
[0023] The optical fiber with a layer of gold nanoparticles self-assembled on the surface is immersed in a sodium chloride polyallylamine hydrochloride solution, then immersed in deionized water, and finally immersed in a sodium chloride sodium polystyrene sulfonate solution; this process is repeated to obtain a spacer layer self-assembled on the surface of the gold nanoparticle layer.
[0024] Since the surface of gold nanoparticles carries a negative charge, and polyallylamine hydrochloride (PAH) carries a positive charge, they will then undergo electrostatic adsorption. Sodium chloride, as an electrolyte, can reduce the ionic strength of the solution, which is conducive to the adsorption of polyallylamine hydrochloride (PAH) and the formation of a stable film. The optical fiber is further placed in deionized water to remove unadsorbed PAH molecules and excess electrolytes, making the film purer and more stable. Finally, the optical fiber is placed in a sodium chloride solution of polystyrene sulfonate. Since polystyrene sulfonate (PSS) carries a negative charge, it will be adsorbed to the surface of gold nanoparticles that have already adsorbed PAH molecules through electrostatic interactions, thereby forming a second layer of film on the surface of gold nanoparticles. Finally, by repeatedly immersing in solutions of PAH and PSS, a multilayer PAH / PSS film can be formed on the surface of gold nanoparticles, and the polymer film can be used as a spacer between the metal and the fluorescent group to effectively prevent the quenching of the fluorescent group and improve the stability and sensitivity of the fluorescent signal.
[0025] As a preferred embodiment of the present technical solution, in the polyallylamine hydrochloride solution of sodium chloride, the concentration of polyallylamine hydrochloride is 0.5-2.0 mg / mL, and the immersion time is 10-20 min.
[0026] As a preferred embodiment of the present technical solution, in the sodium chloride sodium polystyrene sulfonate solution, the concentration of sodium polystyrene sulfonate is 0.5-2.0 mg / mL, and the immersion time is 10-20 min.
[0027] In a second aspect, the present invention further discloses a fluorescence detection system, which includes an FPGA processing module, a voltage processing module, an SD card module, an RGB screen display module and the optical fiber fluorescence sensor according to any one of claims 1-9.
[0028] In the portable fluorescence detection system based on FPGA of the present invention, FPGA provides the overall processing function; the voltage processing module converts the analog signal transmitted by the optical fiber fluorescence sensor into a digital signal using the XADC built into the FPGA, and performs filtering processing; the SD card module is used to store various data such as the system interface; and the RGB screen display module provides the display function.
[0029] In addition, in order to realize the recognition of different fluorescent substances, replaceable LED power supply and filter hole are designed. The fluorescence detection system can realize the miniaturization and portability of fluorescence detection.
[0030] The optical fiber fluorescence sensor of the present invention has at least the following beneficial effects:
[0031] The optical fiber fluorescence sensor of the present invention is a tapered optical fiber sensor, and the tapered optical fiber surface of the optical fiber sensor is self-assembled with a gold nanoparticle layer, and the surface of the gold nanoparticle layer is self-assembled with a spacer layer, wherein, in the gold nanoparticle layer, the spacing of the gold nanoparticles is 50-70nm, and the thickness of the spacer layer is 5-15nm. The present invention first designs the structure of the optical sensor, and uses the evanescent field generated by the tapered optical fiber side wall to excite the gold nanoparticles assembled on the optical fiber surface to generate localized surface plasmon resonance LSPR, thereby generating a very strong regional electromagnetic field, and improving the signal-to-noise ratio of the sensor; secondly, by controlling the spacing of the gold nanoparticles on the surface of the tapered optical fiber side wall, the arrangement problem of the gold nanoparticles is solved, so that the coupling of the resonance field of the LSPR with the fluorescence and the optical fiber is optimized; finally, the spacer layer is assembled on the surface of the gold nanoparticle layer by using the layer-by-layer self-assembly method, so as to solve the problem of quenching of the fluorescent group caused by the resonance energy transfer between the gold nanoparticles and the fluorescent group when the spacing is too small. Therefore, the fiber optic fluorescence sensor of the present invention effectively solves the shortcomings of low signal-to-noise ratio and poor sensitivity of traditional fiber optic fluorescence sensors. Compared with traditional fiber optic fluorescence sensors, the detection signal-to-noise ratio can be increased by 2-3 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 The geometry of the tapered optical fiber is prepared for the present invention;
[0034] Figure 2 A schematic diagram of the self-assembly of layers of polymers on the surface of a tapered optical fiber according to the present invention;
[0035] Figure 3 This is an electron microscope image of the surface of the tapered optical fiber without gold particles prepared in the present invention;
[0036] Figure 4 The electron microscope pictures of the tapered optical fiber surface after being soaked in gold nanoparticles of different concentrations in the present invention;
[0037] Figure 5 This is a comparison chart of the fluorescence intensity of the tapered optical fiber sensors prepared in Comparative Example 1 and Comparative Example 2 of the present invention;
[0038] Figure 6 This is a comparison diagram of the fluorescence intensity of the tapered optical fiber sensor prepared in the comparative example 1 and the example 1 of the present invention;
[0039] Figure 7 It is a schematic diagram of the framework of the fluorescence detection system of the present invention;
[0040] Figure 8 It is the display interface of the fluorescence detection system of the present invention;
[0041] Fig. 9 It is a schematic diagram of the fluorescence enhanced optical fiber sensing detection device of the present invention. DETAILED DESCRIPTION
[0042] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0043] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] S1. First, the optical fiber surface of the optical fiber fluorescence sensor is treated with piranha solution to remove organic matter on the optical fiber surface and hydroxylate the optical fiber surface, thereby improving its hydrophilicity and improving the surface foundation for subsequent modification;
[0047] S2, soaking the surface hydroxylated optical fiber in a tetrahydrofuran solution with a polystyrene-b-poly(4-vinylpyridine) concentration of 0.005 mg / mL and soaking it at 25°C for 10 minutes, so that the polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) molecules can be adsorbed on the surface of the light and form a monolayer; then taking out the optical fiber, washing it with a suitable solvent to remove the unadsorbed polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) molecules; then further soaking the optical fiber in a solution of spherical gold nanoparticles with a concentration of 0.004 mg / mL and soaking it at 25°C for 10 minutes, so that the spherical gold nanoparticles can be adsorbed on the monolayer of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) on the surface of the optical fiber and form a self-assembled monolayer; then taking out the optical fiber, washing it with a suitable solvent to remove the unadsorbed gold nanoparticles;
[0048] S3. Immerse the optical fiber with a layer of gold nanoparticles self-assembled on the surface in a polyallylamine hydrochloride solution of sodium chloride for 15 minutes, then immerse it in deionized water, and finally immerse it in a polystyrene sodium sulfonate solution of sodium chloride for 15 minutes, wherein the concentration of polyallylamine hydrochloride in the polyallylamine hydrochloride solution of sodium chloride is 1.0 mg / mL; the concentration of sodium polystyrene sodium sulfonate in the polyallylamine hydrochloride solution of sodium chloride is 1.0 mg / mL; and this process is repeated to self-assemble two polymer layers on the surface of the gold nanoparticle layer to form a spacer layer.
[0049] Example 2
[0050] S1. First, the optical fiber surface of the optical fiber fluorescence sensor is treated with piranha solution to remove organic matter on the optical fiber surface and hydroxylate the optical fiber surface, thereby improving its hydrophilicity and improving the surface foundation for subsequent modification;
[0051] S2, soaking the surface hydroxylated optical fiber in a tetrahydrofuran solution with a polystyrene-b-poly(4-vinylpyridine) concentration of 0.002 mg / mL, and soaking it at 25°C for 15 minutes, so that the polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) molecules can be adsorbed on the surface of the light and form a monolayer; then taking out the optical fiber, washing it with a suitable solvent to remove the non-adsorbed polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) molecules; then further soaking the optical fiber in a solution of spherical gold nanoparticles with a concentration of 0.001 mg / mL, and soaking it at 25°C for 15 minutes, so that the spherical gold nanoparticles can be adsorbed on the monolayer of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) on the surface of the optical fiber and form a self-assembled monolayer; then taking out the optical fiber, washing it with a suitable solvent to remove the non-adsorbed gold nanoparticles;
[0052] S3. Immerse the optical fiber with a layer of gold nanoparticles self-assembled on the surface in a polyallylamine hydrochloride solution of sodium chloride for 20 minutes, then immerse it in deionized water, and finally immerse it in a polystyrene sodium sulfonate solution of sodium chloride for 20 minutes, wherein the concentration of polyallylamine hydrochloride in the polyallylamine hydrochloride solution of sodium chloride is 0.5 mg / mL; the concentration of sodium polystyrene sodium sulfonate in the polyallylamine hydrochloride solution of sodium chloride is 0.5 mg / mL; and this process is repeated to obtain three polymer layers self-assembled on the surface of the gold nanoparticle layer to form a spacer layer.
[0053] Example 3
[0054] S1. First, the optical fiber surface of the optical fiber fluorescence sensor is treated with piranha solution to remove organic matter on the optical fiber surface and hydroxylate the optical fiber surface, thereby improving its hydrophilicity and improving the surface foundation for subsequent modification;
[0055] S2, soaking the surface hydroxylated optical fiber in a tetrahydrofuran solution with a polystyrene-b-poly(4-vinylpyridine) concentration of 0.010 mg / mL and soaking it at 25°C for 5 minutes, so that the polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) molecules can be adsorbed on the surface of the light and form a monolayer; then taking out the optical fiber, washing it with a suitable solvent to remove the non-adsorbed polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) molecules; then further soaking the optical fiber in a solution of spherical gold nanoparticles with a concentration of 0.008 mg / mL and soaking it at 25°C for 5 minutes, so that the spherical gold nanoparticles can be adsorbed on the monolayer of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) on the surface of the optical fiber and form a self-assembled monolayer; then taking out the optical fiber, washing it with a suitable solvent to remove the non-adsorbed gold nanoparticles;
[0056] S3. Immerse the optical fiber with a layer of gold nanoparticles self-assembled on the surface in a polyallylamine hydrochloride solution of sodium chloride for 10 minutes, then immerse it in deionized water, and finally immerse it in a polystyrene sodium sulfonate solution of sodium chloride for 10 minutes, wherein the concentration of polyallylamine hydrochloride in the polyallylamine hydrochloride solution of sodium chloride is 2.0 mg / mL; the concentration of sodium polystyrene sodium sulfonate in the polyallylamine hydrochloride solution of sodium chloride is 2.0 mg / mL; and this process is repeated to obtain two polymer layers self-assembled on the surface of the gold nanoparticle layer to form a spacer layer.
[0057] Example 4
[0058] S1. First, the optical fiber surface of the optical fiber fluorescence sensor is treated with piranha solution to remove organic matter on the optical fiber surface and hydroxylate the optical fiber surface, thereby improving its hydrophilicity and improving the surface foundation for subsequent modification;
[0059] S2, soaking the surface hydroxylated optical fiber in a tetrahydrofuran solution with a polystyrene-b-poly(4-vinylpyridine) concentration of 0.008 mg / mL, and soaking it at 25°C for 10 minutes, so that the polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) molecules can be adsorbed on the surface of the light and form a monolayer; then taking out the optical fiber, washing it with a suitable solvent to remove the non-adsorbed polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) molecules; then further soaking the optical fiber in a solution of spherical gold nanoparticles with a concentration of 0.006 mg / mL, and soaking it at 25°C for 12 minutes, so that the spherical gold nanoparticles can be adsorbed on the monolayer of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) on the surface of the optical fiber and form a self-assembled monolayer; then taking out the optical fiber, washing it with a suitable solvent to remove the non-adsorbed gold nanoparticles;
[0060] S3. Immerse the optical fiber with a layer of gold nanoparticles self-assembled on the surface in a polyallylamine hydrochloride solution of sodium chloride for 15 minutes, then immerse it in deionized water, and finally immerse it in a polystyrene sodium sulfonate solution of sodium chloride for 15 minutes, wherein the concentration of polyallylamine hydrochloride in the polyallylamine hydrochloride solution of sodium chloride is 1.5 mg / mL; the concentration of sodium polystyrene sodium sulfonate in the polyallylamine hydrochloride solution of sodium chloride is 1.5 mg / mL; and this process is repeated to obtain two polymer layers self-assembled on the surface of the gold nanoparticle layer to form a spacer layer.
[0061] Comparative Example 1
[0062] This control example is a blank tapered optical fiber.
[0063] Comparative Example 2
[0064] This comparative example is substantially the same as Example 1, except that this comparative example only includes one spacer layer.
[0065] Figure 1 This is the geometric structure of the tapered optical fiber prepared in the present invention, wherein L is 300um, L1 is 2mm, and D is 39um.
[0066] Figure 2 This is a schematic diagram of the self-assembly of polymers layer by layer on the surface of a tapered optical fiber according to the present invention.
[0067] Figure 3 This is an electron microscope image of the surface of the tapered optical fiber without gold particles prepared in the present invention. Figure 4 The electron microscope pictures of the tapered optical fiber surface after being immersed in gold nanoparticles of different concentrations according to the present invention are shown.
[0068] Depend on Figure 4It can be seen that the concentration of the best gold nanoparticle solution of the present invention is 0.004 mg / mL.
[0069] The signal-to-noise ratio (SNR) is the power ratio of the signal to the noise, and is an important parameter for measuring signal quality. In the process of spectrometer testing fluorescence intensity, the higher the signal-to-noise ratio, the stronger the signal and the lower the noise, thus the higher the accuracy of the test.
[0070] In order to study the sensitivity of the tapered optical fiber sensor prepared by the present invention, in the experiment of testing the fluorescence intensity by spectrometer, the fluorescein (such as R6G) is adsorbed on the surface of the optical fiber by electrostatic adsorption, and the specific method is as follows:
[0071] After the bare optical fiber in Control Example 1 is corroded by piranha solution (a mixture of concentrated sulfuric acid and hydrogen peroxide), hydroxyl groups are generated on the surface of the optical fiber, which becomes negatively charged. The optical fiber is further immersed in a positively charged R6G solution, and due to electrostatic effects, the R6G molecules are adsorbed onto the negatively charged surface of the optical fiber.
[0072] The outermost layer of the optical fiber in Example 1 and Comparative Example 2 is a PSS layer, which is negatively charged. When the optical fiber is immersed in a positively charged R6G solution, the R6G molecules will be adsorbed onto the negatively charged optical fiber surface due to electrostatic effects.
[0073] Depend on Figure 5-6 It can be seen that the fluorescence intensity of the optical fiber with a gold nanoparticle layer and a polymer layer self-assembled on the surface is increased by about 0.2 times compared with the bare optical fiber; the fluorescence intensity of the optical fiber with a gold nanoparticle layer and two polymer layers self-assembled on the surface is increased by about 2.5 times compared with the bare optical fiber.
[0074] Figure 7 The portable fluorescence detection system based on FPGA is constructed in this invention, wherein FPGA provides overall processing function; voltage processing module converts analog signal from optical fiber fluorescence sensor into digital signal by using XADC built in FPGA, and performs filtering process; SD card module is used to store various data such as system interface; RGB screen display module provides display function (system interface such as Figure 8 ).
[0075] Fig. 9 This is a schematic diagram of the fluorescence enhanced optical fiber sensing detection device of the present invention, which mainly includes a light source, a spectrometer, an optical fiber coupler, an optical fiber sensor, etc.
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An optical fiber fluorescence sensor, characterized in that: The optical fiber fluorescence sensor is a tapered optical fiber sensor, and a gold nanoparticle layer is self-assembled on the surface of the tapered optical fiber of the optical fiber fluorescence sensor, and a spacer layer is self-assembled on the surface of the gold nanoparticle layer. Wherein, in the gold nanoparticle layer, the spacing between the gold nanoparticles is 50-70 nm, and the thickness of the spacing layer is 5-15 nm.
2. The optical fiber fluorescence sensor according to claim 1, characterized in that: The material of the spacer layer is polyallylamine hydrochloride / sodium polystyrene sulfonate.
3. The optical fiber fluorescence sensor according to claim 1, characterized in that: The cone waist length of the optical fiber fluorescence sensor is 200-400 μm, and the detection area length is 1-3 mm.
4. The optical fiber fluorescence sensor according to claim 1, characterized in that: The preparation of the gold nanoparticle layer comprises the following steps: S1, treating the optical fiber surface of the optical fiber fluorescence sensor to hydroxylate the optical fiber surface; S2. The surface hydroxylated optical fiber is sequentially immersed in a tetrahydrofuran solution of polystyrene-b-poly(4-vinylpyridine) and a spherical gold nanoparticle solution to obtain a gold nanoparticle layer by self-assembly on the surface of the optical fiber.
5. The optical fiber fluorescence sensor according to claim 4, characterized in that: The concentration of the tetrahydrofuran solution of polystyrene-b-poly(4-vinylpyridine) is 0.002-0.010 mg / mL, the immersion temperature is 20-30° C., and the immersion time is 5-15 min.
6. The optical fiber fluorescence sensor according to claim 4, characterized in that: The concentration of the spherical gold nanoparticle solution is 0.001-0.008 mg / mL, the immersion temperature is 20-30° C., and the immersion time is 10-15 h.
7. The optical fiber fluorescence sensor according to claim 1, characterized in that: The preparation of the spacer layer comprises the following steps: The optical fiber with a layer of gold nanoparticles self-assembled on the surface is immersed in a sodium chloride polyallylamine hydrochloride solution, then immersed in deionized water, and finally immersed in a sodium chloride sodium polystyrene sulfonate solution; this process is repeated to obtain a spacer layer self-assembled on the surface of the gold nanoparticle layer.
8. The optical fiber fluorescence sensor according to claim 7, characterized in that: In the polyallylamine hydrochloride solution of sodium chloride, the concentration of polyallylamine hydrochloride is 0.5-2.0 mg / mL, and the immersion time is 10-20 minutes.
9. The optical fiber fluorescence sensor according to claim 7, characterized in that: In the sodium chloride sodium polystyrene sulfonate solution, the concentration of sodium polystyrene sulfonate is 0.5-2.0 mg / mL, and the immersion time is 10-20 minutes.
10. A fluorescence detection system, characterized in that: It comprises an FPGA processing module, a voltage processing module, an SD card module, an RGB screen display module and the optical fiber fluorescence sensor according to any one of claims 1 to 9.